2020
DOI: 10.3390/rs12081333
|View full text |Cite
|
Sign up to set email alerts
|

Tree, Shrub, and Grass Classification Using Only RGB Images

Abstract: In this work, a semantic segmentation-based deep learning method, DeepLabV3+, is applied to classify three vegetation land covers, which are tree, shrub, and grass using only three band color (RGB) images. DeepLabV3+'s detection performance has been studied on low and high resolution datasets that both contain tree, shrub, and grass and some other land cover types. The two datasets are heavily imbalanced where shrub pixels are much fewer than tree and grass pixels. A simple weighting strategy known as median f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…With heavily imbalanced datasets, the error from the overrepresented classes contributes much more to the loss value than the error contribution from the underrepresented classes. This makes the deep learning method's loss function to be biased toward the overrepresented classes resulting in poor classification performance for the underrepresented classes [50]. One should also pay attention when applying deep learning methods to new applications because one requirement for deep learning is the availability of a vast amount of training data.…”
Section: Non-vegetation Vegetation Mixedmentioning
confidence: 99%
“…With heavily imbalanced datasets, the error from the overrepresented classes contributes much more to the loss value than the error contribution from the underrepresented classes. This makes the deep learning method's loss function to be biased toward the overrepresented classes resulting in poor classification performance for the underrepresented classes [50]. One should also pay attention when applying deep learning methods to new applications because one requirement for deep learning is the availability of a vast amount of training data.…”
Section: Non-vegetation Vegetation Mixedmentioning
confidence: 99%
“…Among this series, DeepLabv3+ combines the advantages of encoderdecoder architecture and atrous spatial pyramid pooling (ASPP), which can capture rich contextual information from plant root images at various resolutions and segment clear root loci. Ayhan and Kwan (2020) proposed a DeepLabv3+ network improvement based on a weighting strategy, which is used to segment three vegetation cover types: trees, shrubs, and grasses. They showed that DeepLabv3+ is superior to the most advanced machine learning algorithms, i.e., SVM and random forests, in spatial information extraction and pixel segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, those deep learning methods for object detection using color images can be adapted to land cover classification. Recently, our team initiated an investigation along that direction in [31]. However, those deep learning methods require a lot of training data and may not yield better results when data are scarce, which is the case for the IEEE Houston dataset presented in this paper.…”
Section: Introductionmentioning
confidence: 99%